2011
DOI: 10.1152/physiolgenomics.00171.2010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the genomic structure and function of regions influencing renin and angiogenesis in the SS rat

Abstract: Impaired regulation of renin in Dahl salt-sensitive rats (SS/JRHsdMcwi, SS) contributes to attenuated angiogenesis in this strain. This study examined angiogenic function and genomic structure of regions surrounding the renin gene using subcongenic strains of the SS and BN/NHsdMcwi (BN) rat to identify important genomic variations between SS and BN involved in angiogenesis. Three candidate regions on Chr 13 were studied: two congenic strains containing 0.89 and 2.62 Mb portions of BN Chr 13 that excluded the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 69 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…11 They reported that the SR Renin region increased BP (Δ+30 mmHg; P <0.05) in the SS-13 SR congenic (referred to as S/ren rr ) compared with SS (Figure 2A). 11 Also similar to line 9 13, 14 , the S/ren rr congenic restores plasma renin activity (PRA), 19 angiogenesis, 19 and vasoreactivity, 20 indicating that line 9 and S/ren rr share some functional allele(s), but not all. Most notably, the protective region around Renin (46.1–47.2 Mb) did not offset the hypertensive BP allele(s) in S/ren rr , 11 as was detected in line 9 (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…11 They reported that the SR Renin region increased BP (Δ+30 mmHg; P <0.05) in the SS-13 SR congenic (referred to as S/ren rr ) compared with SS (Figure 2A). 11 Also similar to line 9 13, 14 , the S/ren rr congenic restores plasma renin activity (PRA), 19 angiogenesis, 19 and vasoreactivity, 20 indicating that line 9 and S/ren rr share some functional allele(s), but not all. Most notably, the protective region around Renin (46.1–47.2 Mb) did not offset the hypertensive BP allele(s) in S/ren rr , 11 as was detected in line 9 (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
“…We compared the SS/Jr (used by Jiang et al 11 ), the SS/JrMcwi (used for our SS-13 BN congenics 13 ), the SR, and the BN genomic sequences across the entire 3.7 Mb line 9 congenic interval to identify common and unique variants among the strains (Supplementary Table 2). Across the line 9 interval, only 2 variants (<0.0001%) were polymorphic between SS/Jr and SS/JrMcwi, and therefore, we hereafter use SS to denote both strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations